SUSTAINABLE LIVELIHOODS AND VALUE CHAIN DEVELOPMENT WITH WOMEN ENTREPRENEURS: EVIDENCE AND LESSONS FROM THE CLOTHING BANK, SOUTH AFRICA - Raniga, Tanusha (Social Work, 2023)
Female-headed households often benefit from engaging in sustainable livelihoods and value chain development approaches to enhance income security. In this article, the researcher employs a qualitative methodology to study how women entrepreneurs (N=20) selected from The Clothing Bank solve poverty-related problems. This article discusses three strategies relevant to value chain development: access to assets, dealing with risks when reinvesting capital, and enabling multiple stakeholder support. The article concludes with some considerations to bridge the gap between social work and social entrepreneurship to advance developmental social work research. Keywords: feminisation of poverty, sustaining livelihoods, value chain development, women entrepreneurs, female-headed household